The Hermite polynomials and the Bessel functions from a general point of view - G. Dattoli; H. M. Srivastava; D. Sacchetti (International Journal of Mathematics and Mathematical Sciences)
We introduce new families of Hermite polynomials and of Bessel functions from a point of view involving the use of nonexponential generating functions. We study their relevant recurrence relations and show that they satisfy differential-difference equations which are isospectral to those of the ordinary case. We also indicate the usefulness of some of these new families.